Adapting to Online English Learning: Voices of International Students on Challenges and Opportunities - Azizah Maulina Erzad; Nuskhan Abid (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
The transition to online learning has significantly reshaped the educational experience, offering opportunities and obstacles, particularly for international students. This study explored the perspectives of Thai students in an Indonesian Islamic university, examining the challenges they faced and the potential benefits of online learning. Three international students volunteered to participate in this study. Data was collected through qualitative interviews conducted via Google Forms and WhatsApp. Thematic analysis was used to analyze the data. The findings indicated that students encountered several key challenges, including language barriers, technological accessibility, internet connectivity issues, and motivation levels. Despite these challenges, online learning offers benefits such as flexible learning schedules and broader access to educational resources. This study highlights the need for universities to implement targeted strategies to enhance student engagement and academic achievement. Recommendations include the development of policies that support digital infrastructure, tailored learning methodologies, and initiatives to maintain student motivation. Further research is encouraged to explore practical pedagogical approaches and institutional frameworks that can optimize online learning experiences for international students. This study impacts universities by improving digital infrastructure, enhancing learning strategies, boosting student motivation, and optimizing online education for international students.